Mushroom-like ZnO Nanostructures Grown on Tungsten Substrate - Wu, Xiang; Jia, Boxiang; Qu, Fengyu; Zhao, Quanqin (Current Nanoscience, 2014)
In this work, we have developed a facile but efficient method to prepare mushroom-like Zinc oxide (ZnO) nanostructures with a flat cap in the diameter of around 1μm, by thermal evaporation of the mixture of ZnS and carbon powder on a tungsten substrate. The mushroom-like nanostructures were characterized by using advanced techniques such as scanning electron microscope (SEM), X ray diffraction (XRD) and Raman spectroscopy. The optical properties of such product were also investigated by photoluminescence spectroscopy, revealing a strong green emission band emerged, which may be attributed to the oxygen vacancies and various surface states. Finally the formation and growth mechanisms for the mushroom-like ZnO nanostructures were proposed and discussed.
Keywords: Nanostructures